2022
DOI: 10.3390/ijms23158153
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Sulfatases: Biochemistry, Disease Manifestation, and Therapy

Abstract: Sulfatases are enzymes that catalyze the removal of sulfate from biological substances, an essential process for the homeostasis of the body. They are commonly activated by the unusual amino acid formylglycine, which is formed from cysteine at the catalytic center, mediated by a formylglycine-generating enzyme as a post-translational modification. Sulfatases are expressed in various cellular compartments such as the lysosome, the endoplasmic reticulum, and the Golgi apparatus. The substrates of mammalian sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…The latest study used eukaryotic expressing proteins generated in the Sf9 insect cell line and reported that P. xylostella contains three functional PxGSSs (PxGSS1–3) . On the contrary, for the 17 Sulf genes in humans, no function related to GLs hydrolysis and its corresponding genes have been identified yet . In summary, the findings from these studies strongly indicate that strategic targeting of PxGSSs represents a promising and reliable strategy for managing P. xylostella populations.…”
Section: Sequence Characteristics and Evolution Of Pxgss Genesmentioning
confidence: 95%
“…The latest study used eukaryotic expressing proteins generated in the Sf9 insect cell line and reported that P. xylostella contains three functional PxGSSs (PxGSS1–3) . On the contrary, for the 17 Sulf genes in humans, no function related to GLs hydrolysis and its corresponding genes have been identified yet . In summary, the findings from these studies strongly indicate that strategic targeting of PxGSSs represents a promising and reliable strategy for managing P. xylostella populations.…”
Section: Sequence Characteristics and Evolution Of Pxgss Genesmentioning
confidence: 95%
“…[74][75][76] Their native function is to activate type-I sulfatases via oxidation and subsequent hydrolysis and their deficiency is associated with several diseases. [77,78] Different bacterial FGEs were found to be promiscuous in recognizing their Cys-containing peptide sequence and modified protein with the tag Cxxxx. [79] FGEs' ability to install a bioorthogonal aldehyde functional group have allowed them to mediate ligation reactions [80] including trapped-Knoevenagel ligation [81] using a thiopyrazolone-maytansine and aminooxymaytansine compounds or undergo a hydazino-iso-Pictet-Spengler [82] or reaction with hydrazide-or aminooxy-functionalized reagents.…”
Section: Cysteinementioning
confidence: 99%
“…Aerobic FGEs catalyze the conversion of the thiol side chain of cysteine to an electrophilic aldehyde‐bearing group via copper and oxygen‐dependent catalysis (Figure 3B). [74–76] Their native function is to activate type‐I sulfatases via oxidation and subsequent hydrolysis and their deficiency is associated with several diseases [77,78] . Different bacterial FGEs were found to be promiscuous in recognizing their Cys‐containing peptide sequence and modified protein with the tag Cxxxx [79] .…”
Section: Cysteinementioning
confidence: 99%
“…Lysosomal storage disorders (LSDs) are characterized by an accumulation of unprocessed biochemicals in the lysosome involving 50–60 enzymes [ 57 , 58 , 59 ]. These disorders present CNS, skeletal, and visceral disorders such as hepatomegaly and splenomegaly.…”
Section: Preclinical Studymentioning
confidence: 99%